1998
DOI: 10.1119/1.19050
|View full text |Cite
|
Sign up to set email alerts
|

Triaxial bifurcations of rapidly rotating spheroids

Abstract: A rotating system, such as a star, liquid drop, or atomic nucleus, may rotate as an oblate spheroid about its symmetry axis or, if the angular velocity is greater than a critical value, as a triaxial ellipsoid about a principal axis. The oblate and triaxial equilibrium configurations minimize the total energy, a sum of the rotational kinetic energy plus the potential energy. For a star or galaxy the potential is the self-gravitating potential, for a liquid drop, the surface tension energy, and for a nucleus, t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 7 publications
1
14
0
Order By: Relevance
“…Newton and Maclaurin showed that forces of rotation and gravitation balance in an oblate spheroid shape [41]; this result is confirmed by the shapes of planets and stars. Regarding galaxies, oblate spheroid geometry is compatible with images ( Fig.…”
Section: Poisson's Orbits or Newton-maclaurin's Spin?supporting
confidence: 60%
“…Newton and Maclaurin showed that forces of rotation and gravitation balance in an oblate spheroid shape [41]; this result is confirmed by the shapes of planets and stars. Regarding galaxies, oblate spheroid geometry is compatible with images ( Fig.…”
Section: Poisson's Orbits or Newton-maclaurin's Spin?supporting
confidence: 60%
“…This shape is furthermore evident in images of the Sun and gas giants. Although the triaxial ellipsoidal shapes of Jacobi are permissible [42], the ostensibly circular motions in spiral galaxies indicate the higher symmetry of the oblate suffices.…”
Section: Background: the Equilibrium Shape Of Rotating Gravitating Omentioning
confidence: 99%
“…Maclaurin evaluated the double integral of (9) for the oblate spheroid. The result [42] is simple for homogeneous density:…”
Section: Internal (Self) Vs External Potentialsmentioning
confidence: 99%
“…With increasing angular momentum the Maclaurin spheroidal mass becomes more oblate until it has an eccentricity of 0.8, which is equivalent to an aspect ratio of 0.6. At this point, the Maclaurin spheroid is unstable and with a decrease in angular momentum will become a Jacobi ellipsoid (Eriguchi & Hachisu 1982;Dankova & Rosensteel 1998). Alternatively, we propose that if a Maclaurin spheroid mass has an aspect ratio ≤0.6 and has a circumferential equatorial disk, the Maclaurin spheroid will morphologically form a "steep profile" while angular momentum remains constant.…”
Section: Formation Of a "Steep Profile" In A Maclaurin Spheroid With mentioning
confidence: 99%
“…The first term is the Maclaurin spheroid's self-energy U sph and is a known quantity (Chandrasekhar 1969;Dankova & Rosensteel 1998),…”
Section: Volume Correctionmentioning
confidence: 99%